A business case for 5G services in an industrial sea port area. (April 2022) - Rendon Schneir, Juan; Bradford, Julie; Ajibulu, Ade; Pearson, Ken; Konstantinou, Konstantinos; Osman, Hassan; Zimmermann, Gerd
Abstract: 5G is a technology that was designed to provide citizens with access to faster and innovative wireless services. While different technical aspects related to 5G have been extensively examined by researchers worldwide, a lack in the existing literature is the economics of 5G in terms of business cases of specific 5G use cases. In this article we analyse the business case for three 5G use cases in an industrial sea port area, the Hamburg port in Germany, over the period 2020–2030. The first use case is enhanced mobile broadband and the results show a payback period lower than one year for all the scenarios analysed. The second use case is automation of container handling in the port's container terminal. It was found that the payback period is also lower than one year with a positive business case net present value in all scenarios studied. The business case of the third case, augmented reality for construction projects in the port's area, is challenging as the payback period was 5 years for the baseline case. Moreover, when performing the sensitivity analysis, it was found that in several scenarios there was a negative return on investment, and it was not possible to recover the investment over the time period studied. It can be concluded that mobile network operators will need to be careful as not all new 5G service offerings may have a positive business case. Future research work should focus on studying other 5G use cases in the port area, and on examining other industrial areas beyond ports such as airports, science parks and manufacturing facilities. Highlights: In this article we analyse the business case for three 5G use cases in an industrial sea port area. The area studied was the Hamburg port in Germany over the period 2020–2030. The results show that the business case for a 5G network providing enhanced mobile broadband services alone is positive. The business case of the second 5G use case is positive whereas the business case of the third 5G use case is challenging.